KEBIJAKAN DIVIDEN SEBAGAI PEMEDIASI PENGARUH ANTARA LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN INDEKS LQ 45 - Eka Purnama Sari; Rico Nur Ilham; Debi Eka Putri; Anggraini Syahputri (ITB AAS INDONESIA, 2022)
This study aims to determine dividend policy can be a mediating variable from the influence of leverage and profitability on firm value in LQ 45 index companies. This study uses quantitative research with purposive sampling technique and obtains 80 observational data. Data analysis techniques used include classical assumption test, simple linear regression, correlation coefficient and determination as well as hypothesis testing simultaneously or partially. The results of the study show that leverage and profitability have a significant effect on dividend policy. Profitability and dividend policy have a significant effect while leverage has no significant effect on firm value. Based on the Sobel test, dividend policy is not able to mediate leverage and profitability on firm value.